Examining the predictive power of emotional intelligence on coaching success - Magrum, E. D.; Manninen, M.; Schempp, P. G. (International Sport Coaching Journal, 2024)
Emotional intelligence (EI) is recognized as an indicator of success, yet little research has examined the role of EI in coaching success. This cross-sectional study assessed the power of EI in predicting coaches` career winning percentage in 277 head collegiate coaches including 51 basketball and 226 volleyball coaches. Coaches were on average 41.47 years old (SD = 9.68), had 12.17 years of head coach experience (SD = 9.40), and a career winning percentage of 50.67% (SD = 16.5). Coaches completed an online questionnaire including the Assessing Emotions Scale, which was used to assess their EI. Career winning percentage was calculated by extracting data from institutional websites and NCAA databases. Regression analyses revealed EI was not a significant predictor of coaching success when all coaches were analyzed together, F(4, 272) = 0.7504, p = .5585. However, when examined separately, EI was a significant predictor of basketball coaches` success, F(4, 46) = 2.678, p = .0433, but not volleyball coaches` success, F(4, 221) = 0.363, p = .0835. Thus, the current body of evidence indicates EI has a nonuniform impact on coaching success. While acknowledging sample size limitations, these novel findings nevertheless indicate that EI may disproportionally influence the coaching process and downstream success by sport.